The Influence of Cryptocurrency (Bitcoin), IHSG, Fed Rate, and BI Rate on IDX BUMN 20 Stock Prices: - Royhan Agnia; Arief Bachtiar (PT FORMOSA CENDEKIA GLOBAL, 2023)
The cryptocurrency market has grown significantly in recent years, with Bitcoin emerging as the dominant player. This research aims to investigate the relationship between cryptocurrency (Bitcoin) prices, the Indonesia Stock Exchange Composite Index (IHSG), the Federal Reserve (Fed) Rate, and the Bank Indonesia (BI) Rate with the stock prices of IDX BUMN20 companies. The study adopts a quantitative research approach, utilizing historical time-series data for the variables of interest spanning a specific period. The data will be collected from reputable financial databases and sources. Multiple regression analysis and White analysis causality tests will be employed to examine the potential influence of these factors on IDX BUMN20 stock prices. The findings from this research are expected to shed light on the interconnectedness of the cryptocurrency market with the traditional stock market in Indonesia and provide valuable insights for investors, policymakers, and market participants. Understanding these relationships can aid in risk management strategies and investment decision-making. However, it is crucial to note that the cryptocurrency market is known for its volatility and speculative nature, which may introduce unique challenges in interpreting the results. Therefore, cautious consideration and expert financial advice.